(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In the present manuscript, we introduce a new notion of (β, ϕ)− admissible hybrid contractions in metric spaces and establish fixed point results in the setting of these spaces. The derived results extend the reported findings of the past. The derived result is supplemented with a non-trivial example. We have also analyzed the Ulam-Hyers stability and well-poisedness as an application to the derived results.